DEVELOPMENT STRATEGY FOR MICRO, SMALL AND MEDIUM ENTERPRISES OF PALEMBANG CITY - Novita Wulandari; Bastiar Tambuh; Fitri Herdayani; Yoni Rahayu (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in bolstering the economy, particularly in employment, contributing significantly to the stability of both regional and broader financial systems. This research, employing a qualitative approach involving observation, interviews, and documentation studies, seeks to identify and map potential MSME areas in Palembang City. The study's findings encompass the thorough identification and mapping of these enterprises across each sub-district in Palembang City, elucidating 22 strategic issues such as capital, marketing, infrastructure, licensing, and innovation. Furthermore, the research sheds light on the spatial distribution of MSMEs, categorizing them based on zoning and business type. Notable examples include the culinary business center in Bukit Kecil sub-district, the cracker and kemplang business center in Sukarami sub-district, the songket business center in Ilir Barat II sub-district, and the jumputan business center in Kertapati sub-district. This comprehensive analysis contributes valuable insights into the multifaceted dynamics of MSMEs, offering a foundation for informed policy decisions and strategic planning to enhance economic sustainability.